Analysis of general plans of the USSR universities in 1970–1980 - A. V. Popov; A. A. Semenchukova (Vestnik MGSU)
Introduction. Within the framework of this study, an important and interesting period of the development of higher school architecture in our country is considered, characterized by an integrated approach and the mass introduction of advanced solutions for that time. The topic is particularly relevant nowadays, when the strategy for the future development of university campuses of our country is being determined, the necessity of which is noted in the national project “Science and Universities”, the federal project “Development of infrastructure for scientific research and personnel training” and other documents of the federal and regional levels. Most of the general plans of existing Russian universities were approved during the Soviet period. At the present stage of the development of educational infrastructure in Russia, an important task is to determine the possibilities for further expansion and improvement of higher educational institutions in terms of their architectural and planning features and the potential laid in the master plans of higher educational institutions by architects of the past.Materials and methods. In order to study the design features, characteristic solutions and trends in the architecture of complexes of higher educational institutions of the period under review, the normative documents in force at that time, regulating the design of higher educational institutions, scientific research and manuals for practitioners, project documentation were studied. The emphasis is made on the analysis of general plans and urban planning placement of higher educational institutions in the structure of settlements.Results. A number of characteristic tendencies and solutions used by architects and urban planners are noted. The general methods of forming university complexes in the USSR in the period 1970–1980 are considered. Individual characteristic examples are analyzed and schemes with colour indication of implemented objects of the general plan are given to illustrate the development of universities. Despite the continuing increase in the number of students and the construction of buildings and complexes of higher education that is gaining momentum in the construction, the potential laid down in the general plans of many universities of the period under consideration is still not exhausted. It is possible to note the comprehensive approach of architects of the period to the development of master plans of universities. In accordance with the principles of planning, zoning and spatial connectivity laid down in the Soviet period, university complexes are successfully functioning at the present time.Conclusions. The general plans of universities developed during the Soviet period are characterized by a well-thought-out planning structure that takes into account most of the needs of the average student of that time. Due to the general principles of zoning with the possibility of linear or centric development of each zone, such layouts are focused on dynamic development in space over time with the possibility of adapting to modern requirements of functional filling of individual zones.